2021
DOI: 10.1186/s12882-021-02452-5
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease: prevalence and association with handgrip strength in a cross-sectional study

Abstract: Background Poor physical function is strongly associated with mortality and poor clinical outcomes in adults with chronic kidney disease (CKD). Handgrip strength (HGS) is an important index for physical function in the general population, and the association between HGS and CKD is worth investigating. Methods From September to November 2015, we conducted a cross-sectional study consisting of 10,407 participants in Jurong City, China. Age-related a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“… 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 However, the relationship between handgrip strength or walking pace and the risk of CKD has not been fully investigated. Only a previous cross‐sectional study 31 reported that compared with the lowest sex‐specific handgrip strength tertiles, participants in the moderate (OR, 0.64; 95% CI: 0.49–0.83) and highest tertiles (OR, 0.37; 95% CI: 0.23–0.58) had a lower prevalence of CKD in 10 407 general Chinese participants. Of note, the cross‐sectional design cannot determine temporal and causal relations.…”
Section: Discussionmentioning
confidence: 94%
“… 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 However, the relationship between handgrip strength or walking pace and the risk of CKD has not been fully investigated. Only a previous cross‐sectional study 31 reported that compared with the lowest sex‐specific handgrip strength tertiles, participants in the moderate (OR, 0.64; 95% CI: 0.49–0.83) and highest tertiles (OR, 0.37; 95% CI: 0.23–0.58) had a lower prevalence of CKD in 10 407 general Chinese participants. Of note, the cross‐sectional design cannot determine temporal and causal relations.…”
Section: Discussionmentioning
confidence: 94%
“…There is a significant relation between HGS and kidney function, and it is an useful and straightforward index of muscle weakness [11,12]. Subjects with higher HGS were found to have a lower predominance of CKD, and HGS was observed to be highly related to the reduced rate of CKD in the study conducted by Cheng et al,2021; however, very few survey studies have reported the relationship between CKD and HGS in Chinese society individuals [13]. Latest evidence has previously proven that there is a favorable association between muscle weakness and the incidence of chronic kidney disease (CKD) [14].…”
Section: Discussionmentioning
confidence: 97%
“…Despite this, the association between HGS, the risk of CKD onset and associated allcause mortality remains underexplored. Initially, only a single cross-sectional study has highlighted that individuals in the moderate and highest tertiles for sex-speci c handgrip strength had a reduced prevalence of CKD, compared to those in the lowest tertile 29 . However, the inherent limitations of cross-sectional designs preclude the establishment of temporal and causal relationships.…”
Section: Discussionmentioning
confidence: 99%
“…However, the inherent limitations of cross-sectional designs preclude the establishment of temporal and causal relationships. Moreover, although recent longitudinal cohort studies have identi ed an inverse relationship between grip strength and the risk of CKD, the speci c quantitative impact of HGS on CKD risk remains unexplored 29 . Additionally, substantial evidence connects muscle function with the development of diabetes, lipid disorders, the risk of sudden cardiac death, and overall mortality [30][31][32][33] .…”
Section: Discussionmentioning
confidence: 99%